ANALISIS WEEKEND EFFECT TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA - LUHGIATNO, Bapak (STIE Totalwin Semarang, 2011)
This research investigated the Weekend Effect Phenomenon on stock price whichÂ inclined on Friday and declined on Monday. Thus, we analyzed differences of stock return at that day in Indonesian Stock Exchange. The population was Stock registered in Indonesia Stock Exchange, and the sample wasÂ IHSG and LQ45 Index in Jan 2009 to Des 2010. Dependent Variable wasÂ Stock Return and Independent Variable was Weekend Effect which traded on Friday and Monday. Data used in this study was secondary data from ISX, that is IHSG and LQ45 Index. This research shown that there is no differences between stock return on Friday and Monday in IHSG and LQ45 index. This indicated by value of IHSG was 0.065 > 0.05 and LQ45 index was 0.56 > 0.05.